PENERAPAN METODE PEMBELAJARAN KOOPERATIF TIPE STUDENT TEAM ACHIEVMENT DIVISIONS (STAD) UNTUKMENINGKATKANHASIL BELAJAR IPA SISWA KELAS IVSDN 01 LUBUK MUDA - Triasih, Endang; Syahrilfudin, Syahrilfudin; Lazim. N, Lazim. N (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2017)
Abstract: The background of the problems in this study is the low student learning outcomes IPA. Based on these problems, researchers have conducted research to improve student learning outcomes by implementing cooperative learning methods Student Team Achievement Divisions (STAD). The type of research is classroom action research (PTK), and carried out in two cycles. While the subject of this study is IV.B grade students of SDN 01 Lubuk Young with the number of students 19 people. Results from this study is the increase in the activity of the teacher, student activities, and student learning outcomes. At the first meeting of the first cycle, the percentage of teachers activity of 58.30% with enough categories, at the second meeting increased to 70.50% in both categories. At the first meeting of the second cycle of teachers percentage of 86.50% with a very good category, at the second meeting increased to 95.83% with the category very well. At the student activity also increased, in the first cycle of the first meeting of the percentage of 62% with good category, at the second meeting increased to 75% in both categories. At the first meeting of the second cycle percentage of 87.50% with a very good category, and at the second meeting increased to 91.67% with the category very well. On student learning outcomes also increased with an average score of students before action is 66.15, the first cycle increased to 70.52. And on the second cycle increased again to 80.26.Keywords: Cooperative Learning Model Student Team Achievement Divisions (STAD), IPA Learning Outcomes